2013
DOI: 10.5534/wjmh.2013.31.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Symptoms (LUTS) Secondary to Benign Prostatic Hyperplasia (BPH) and LUTS/BPH with Erectile Dysfunction in Asian Men: A Systematic Review Focusing on Tadalafil

Abstract: This review assesses lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) with or without erectile dysfunction (ED) and related therapies focusing on tadalafil. A literature search was obtained and reviewed for the epidemiology, treatment therapies, pathophysiology, and efficacy and safety of phosphodiesterase type 5 inhibitor (PDE5i) tadalafil in patients with LUTS/BPH. Approximately 42% of men aged 51 to 60 years have BPH. Approximately 90% of men aged 45 to 80 years have LUTS. Occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 77 publications
(170 reference statements)
1
37
0
5
Order By: Relevance
“…As recently described in the literature, ED and LUTS associated with BPH are widespread urological conditions in elderly subjects. The association between ED and LUTS/BPH and the increasing prevalence of each clinical condition has been previously shown in several population‐based epidemiological studies and summarised in a recent systematic review . Placebo‐controlled randomised studies have confirmed that Tadalafil (a PDE5i) is efficacious and safe in treating men with either ED or LUTS/BPH or in men presenting with both .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As recently described in the literature, ED and LUTS associated with BPH are widespread urological conditions in elderly subjects. The association between ED and LUTS/BPH and the increasing prevalence of each clinical condition has been previously shown in several population‐based epidemiological studies and summarised in a recent systematic review . Placebo‐controlled randomised studies have confirmed that Tadalafil (a PDE5i) is efficacious and safe in treating men with either ED or LUTS/BPH or in men presenting with both .…”
Section: Discussionmentioning
confidence: 75%
“…Similar results were obtained in both the QPT test and QoL among the two groups of study (QPT: 2.58±0.07 vs 2.04±0.06; P<.0001; QoL: 3.94±0.14 vs 2.38±0.14; P<.0001, in groups A and B, respectively). At 6 months of follow-up, the improvement observed in the self-administered questionnaires was related to a significant increase in the Qmax values (mean 11.34±0.35 mL/s vs 17.07±0.35 mL/s; P<.0001) and to a lower postvoid residual (116.65±5.51 mL vs 61.8±5.51 mL, P<.0001), in the two groups A and B, respectively.As recently described in the literature, ED and LUTS associated with BPH are widespread urological conditions in elderly subjects.The association between ED and LUTS/BPH and the increasing prevalence of each clinical condition has been previously shown in several population-based epidemiological studies 4,30-32 and summarised in a recent systematic review 33. Placebo-controlled randomised studies have confirmed that Tadalafil (a PDE5i) is efficacious and safe in treating men with either ED or LUTS/BPH or in men presenting with both 15,[34][35][36][37].…”
mentioning
confidence: 80%
“…Various clinical studies have shown that PDE5 inhibitors such as tadalafil, sildenafil, and vardenafil have therapeutic effects on LUTS, possibly as a consequence of increased pelvic organ blood flow/perfusion in the lower urinary tract. 12 PDE5 inhibitors also appear to modulate afferent activity, 12,41 upregulate cyclic guanosine monophosphate (cGMP)/protein kinase G (PKG) activity, 12,42 downregulate Rho kinase activity, 42,43 and possibly reduce inflammation. 44 In a repeat of our previous study in rats with chronic bladder ischemia, we showed that the addition of tadalafil protects bladder function and morphology, resulting in decreased bladder hyperactivity.…”
Section: Pde5 Inhibitorsmentioning
confidence: 99%
“…IPSS is divided into three domains: obstructive symptom (incomplete emptying, weak stream, intermittency, and straining), irritative symptom (urgency, voiding frequency, and nocturia), and IPSS-QoL. The total score of seven IPSS questions allowed to classify the patients into the low score range (0-7), intermediate score range (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and high score range (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The 8th question, regarding the patient's quality of life (QoL), was considered separately, with a score ranging from 1 to 6 (0-delighted to 6-terrible).…”
Section: Methodsmentioning
confidence: 99%